Segmentasi Area KTP dari Image untuk Otomatisasi Pembacaan Data - Jonathan Hans Soeseno; Liliana Lililana (Jurnal Infra, 2017)
Datas which are stored in Indonesia National ID Card are common usually used in several administration process. In order to be able to extract the data a program which can segment the ID card area out of an image is needed.The first step of this method is to extract only the area of National ID Card. The area of National ID Card is determined using blueness level of every pixel. Then Canny Edge Detection is used to mark the edges of National ID Card, which later processed by using dilation to thicken the edges. The next step involves converting the image into binary image. By dividing each edge into twelve partitions and using lines to mark each edge. That way the area of National ID Card is extracted from the image by using certain fixed ratio.The application which is used in this paper can determine the area of National ID Card successfully regardless of skew and rotation, yet the application fails to determine the area of National ID Card when there exist an object with similar color to the National ID Card.